Effect of forest composition on bird species abundance in tropical dry deciduous forest: A case of Bhimbandh Wildlife Sanctuary, India - MOHD SHAHNAWAZ KHAN (Society for Indonesian Biodiversity, 2017)
Abstract. Khan MS. 2017. Effect of forest composition on bird species abundance in tropical dry deciduous forest: A case of Bhimbandh Wildlife Sanctuary, India. Biodiversitas 18: 78-85. The tropical dry deciduous forest (TDDF) with 38.2% of total forest cover in India forms the largest forest type of India. TDDF have been managed for centuries in the Indian subcontinent. However, so far it is not clear how different forest compositions and structures inï¬‚uence the abundance and the distribution patterns of faunal species vice versa. To provide further insights in this respect, we analysed how different habitat variables inï¬‚uence the abundance and diversity of forest birds. The difference in relative species abundances and habitat separation between forest specialist and generalist birds was also investigated. Different classes of bird density were discriminated with habitat variables. In general, it was found that higher bird densities were concentrated in the lower tree and shrub densities and diversities, however, high grass density and diversity with low tree density and diversity favoured the overall high bird density. Results further indicate the positive association of relative density of specialist bird species with the high grass density and diversity and low tree density and diversity. Specialists occurred in the lower relative densities (0.75Â±0.68) than that of generalists (0.86Â±0.69) and were found restricted to dense, pristine woody forest patches with high tree diversity. Keywords: Bhimbandh Wildlife Sanctuary, birds, Forest Composition, India, Tropical Dry Deciduous Forest